Improved Draft Genome Sequence of Pseudomonas poae A2-S9, a Strain with Plant Growth-Promoting Activity - Xia, Ye (Microbiol Resour Announc, 2019)
We report here the improved draft genome sequence of Pseudomonas poae strain A2-S9, a bacterium that was originally isolated from switchgrass plants and exhibited the capacity for plant growth promotion. Its genome has a size of 6.68 Mbp and a GC content of 61.3%. The genome encodes 6,022 predicted protein-coding genes.